Appropriate imaging in the management of first branchial cleft anomalies - Koento, Trimartani; Sari, Indira (PERHATI-KL, 2023)
Background: First branchial cleft anomalies (FBCA) are rare clinical entities of the head and neck.The low incidence and varied presentation often result in misdiagnosis and inappropriate treatment.Correct diagnosis is essential for proper management, while an incorrect diagnosis will often lead toinadequate treatment. A good understanding of the regional anatomy and embryology can lead to anearly diagnosis and thereby effective management of FBCA. Purpose: To present how to diagnose andmanage FBCA. Case report: A case of a 6-year-old female who had an FBCA with a history of swellingand recurrent discharge from the fistula in the infra-auricular area. Complete excision of the tract wasperformed without facial nerve complication. Clinical question: What is the appropriate imaging fordiagnosis FBCA? Review method: Scoping review was done to identify the scientific evidence aboutimaging for diagnosis FBCA. Systemic searching in 4 databases (PubMed, Embase, Proquest, and Webof Science) using keywords “first branchial cleft”, “anomaly”, and “imaging”. Result: Three article wasfound relevant with the topic of imaging for diagnosis FBCA. Conclusion: Proper diagnosis of FBCAcan lead to proper management and good results. Imaging can provide an anatomical picture of eachbranchial arch anomaly, which can be very helpful in preoperative planning to determine a definitivesurgical approach. Early management of FBCA can reduce the recurrence rate significantly.Keywords: first branchial cleft, anomaly, children, imaging